Combination of Calotropis gigantea Radix Extract and Artemisin as an Antimalarial Agent Against Plasmodium berghei - Hayati, Elok Kamilah; Fatati, Asnal; Muti’ah, Roihatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Calotropis gigantea radix is one of plant which has bioactive component as antimalarial.The purpose of this research are to know antimalarial activity from combination of Calotropis gigantea radix extract and artemisin. The research consist of extraction of Calotropis gigantea radix was done with extraction maseration method. Extraction was performed by maseration with 80% ethanol solvent. Concentrated extract was in vivo antimalarial tested to animal model. Mice were peritoneal infected with 106Plasmodium berghei ANKA and divided into 5 treatment groups: negative control; positive control (artemisin of dose 4 mg/kgBW); combination of artemisin(1/4 dose of artemisin standar) and Calotropis giganteain 3 doses: 0,1 mg/KgBW; 1 mg/KgBWand 10 mg/KgBW. Data of inhibition was analyzed using SPSS program with Two Way ANOVA Test dan continued with Tukey Test.The result shows that combination of Calotropis gigantea radix extract and artemisin with dose 10 mg/KgBB has higher antimalarial activity than control positive (artemisin). The value of parasite inhibition is 55,2% for dose 0.1 mg/KgBW ; 72,8% for dose 1 mg/KgBW ; 87,3% for dose 10 mg/KgBW and 56,06 mg/KgBW for control positive (artemisin). The phytochemical compounds in 80% ethanol solvent extract are tannins and steroids. Keywords: Calotropis gigantea,antimalaria, combination, artemisin, Plasmodium berghei